Evaluasi Penerapan ISO 9001:2015 pada CV. Indo Metal Forming (IMF) - Nico Karman; Jani Rahardjo (Jurnal Titra, 2021)
The evaluation process on ISO 9001:2015 application in CV. IMF (Indo Metal Forming) was done by doing fulfillment on 10 CV. IMF (Indo Metal Forming)'s invention.  10 problem was come from the results of external audit on October 2020. On the fulfillment proccess everything is pointing to the clause in the ISO 9001:2005 document. CV. IMF (Indo Metal Forming)'s 10 invention everything already fulfilling the clauses.  The fulfilment process that was done was based from the cause or the root of the problems that was reviewed through root cause analysis method. Every fulfilment is already submitted to the company. The fulfilment document can be applied to the company for their management or production process. The fulfilment document is already explained to the company. The plan's document was already verified through the authorized person of the company. All the problem that has been solved, will be the requirement of company to start the next internal audit.